Acurácia dos indicadores clínicos do diagnóstico de enfermagem falta de adesão em pessoas vivendo com AIDS - Costa, Mayara Mirna do Nascimento (2016)
In the early 1990s, a major milestone in the treatment of Acquired Immune Deficiency Syndrome was the development of highly active combination antiretroviral therapy. The great benefit generated by the use of this therapy was prolonging the survival of the people who got this disease, since it is no longer considered fatal, becoming a chronic condition. Despite improvements generated by this therapy, there are still many difficulties to be overcome. One is the patient adherence to their treatment, bringing challenges to services and health professionals. Hence the need for early identification of nursing diagnosis Lack of Accession so that solutions are sought by the nurse with the patient and his family. With this problem, adds to the difficulty of hospital nurses in inferring that diagnosis, especially in identifying their defining characteristics. In this context, the objective was to evaluate the accuracy of clinical indicators of nursing diagnosis Lack of Adherence to antiretroviral treatment for people living with the Acquired Immunodeficiency Syndrome. The research took place in two stages. The first consists of the evaluation of the diagnostic indicators in the study; and second, the diagnostic inference performed by specialist nurses. The first step took place in a referral hospital in the treatment of infectious diseases in the Northeast of Brazil, and data were collected through an instrument for carrying out history and physical examination and analyzed for the presence or absence of the diagnostic indicators. In the second stage, the data were sent to experts, who judged the presence or absence of the diagnosis in the studied clientele. The project was submitted to the Ethics Committee of the Federal University of Rio Grande do Norte, obtaining approval with the General Certificate for Ethics Assessment (CAAE) No 46206215.3.0000.5537. Data were analyzed using descriptive and inferential statistics. Test were used Fisher's exact, chi-square test of Pearson and logistic regression. Since the accuracy of clinical indicators was measured by sensitivity, specificity, predictive values, likelihood ratios. As a result, we identified the presence of diagnosis Lack of Accession on 69% (n = 78) of the study patients. The defining characteristics that showed statistically significant association with the diagnosis studied were: lack of adherence behavior, complications related to development, missing scheduled appointments, failure to achieve results, and exacerbation of symptoms. The characteristic with greater sensitivity was missing scheduled appointments and the highest specificity behavior of noncompliance. The logistic regression showed as predictors for the diagnosis Lack of Accession: lack of adherence behavior, missing scheduled appointments, failure to achieve results, and exacerbation of symptoms. It was concluded that the identification of clinical indicators accurately enabled a good prediction of the nursing diagnosis Lack of Accession on people living with the Acquired Immune Deficiency Syndrome, helping nurses develop early on strategies for promoting adherence to the use of antiretrovirals.